Changes in the thermal growing season in Nordic countries during the past century and prospects for the future - Carter, Timothy R. (Agricultural and Food Science, 1998)
The start, end, duration and intensity of the thermal growing season (the period with mean daily temperatures exceeding 5°C) during the past century (1890-1995) was analysed at nine sites in the Nordic region. Statistical comparisons were made between three adjacent 35-year periods. The results indicate that the growing season lengthened considerably at all sites between 1891-1925 and 1926-1960. Lengthening has continued at a slower rate up to the present at the eight Fennoscandian sites but not at the Icelandic site. In contrast, the intensity of the growing season, expressed by effective temperature sum above 5°C, which increased at all sites between the first two periods, has decreased slightly at all locations except Turku in recent decades. Under three scenarios, representing the range of estimated greenhouse gas-induced warming by the 2050s, the growing season is expected to lengthen at all sites. For a “Central” scenario, the greatest lengthening is computed for southern and western Scandinavia (7-8 weeks) with smaller changes in Finland (4 weeks) and Iceland (3 weeks). With a lengthening growing season during the past century in Fennoscandia, there are likely to have been impacts on natural and managed ecosystems. Some evidence of recent biotic and abiotic effects already exists, but other indicators of long-term change remain to be analysed.